Maquila, currency misalignment and export-led growth in Mexico - Carlos A. Ibarra (CEPAL Review, 2011)
The paper argues that the weak effect of exports on gdp growth in Mexico is partly explained by two features of the Mexican economy that arose subsequent to trade liberalization: the peso’s continued real appreciation and the large and rising share of the maquila sector in manufacturing exports. The argument is developed through an analytical example for a stationary economy with no investment. As motivation for the example’s main assumptions, the paper presents empirical evidence gathered from the country’s Annual Industrial Survey and the estimation of cointegration equations for maquila and non-maquila intermediate imports. The empirical evidence shows that (a) exports are highly dependent on imports and thus benefit from trade liberalization, and (b) while real exchange rate changes can induce substitution between local and imported intermediate goods generally, this is not the case in the maquila sector.